The Globalization of Martial Arts: The Change of Rules for New Markets (Revista de Artes Marciales Asiáticas, 2012)
The rapid growth of the martial arts industry warrants a deeper understanding of the globalization process of martial arts. There is very little known about martial arts as a global consumer product and its diffusion process to date. In this article, the authors discuss the global expansion and integration of Asian martial arts. Such factors as sportification and standardization are closely examined as significant driving forces for the growth of the martial arts industry. This article also examines several important issues, such as the political environment, culture, and market strategies, in terms of their influence on the development and the martial arts’ industry future growth. This study concludes with a discussion of challenges and future opportunities for development.